The contribution of intangible assets to sectoral productivity growth in the EU - Thomas Niebel; Mary O'Mahony; Marianne Saam (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
In this paper we report on new data on intangible investment at the level of 1-digit NACE industries of 10 EU countries. The data are constructed as a sectoral breakdown of the INTANInvest database, which contains measures of intangible investment at the level of the aggregate business sector. With the sectoral data we assess the contribution of intangibles to productivity growth based on growth accounting and econometric estimation of production functions. The growth accounting contribution of intangibles to labor productivity growth is generally highest in manufacturing and finance. The estimated output elasticity of intangibles lies between 0.1 and 0.2, considerably below values found in previous research using aggregate data.
Keywords: E22; J24; O47; 330; Intangible Assets; Labor Productivity; Growth Accounting; Panel Regressions